2010
DOI: 10.1039/c0jm01527j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical ascorbic acid sensor based on DMF-exfoliated graphene

Abstract: This paper describes the electron transfer properties of graphene nano-sheets (GNSs) immobilised on pyrolysed photoresist film (PPF) electrodes. The former are produced by the dispersion and exfoliation of graphite in dimethylformamide, and they are characterised using transmission electron microscopy, scanning electron microscopy and Raman spectroscopy. Cyclic voltammetry and electrochemical impedance spectroscopy are used to quantify the effect of the GNSs on electrochemical surface area and on electron tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(104 citation statements)
references
References 42 publications
1
103
0
Order By: Relevance
“…However, such methodologies just shift the rate-limiting step from exfoliation to intercalation, limiting the potential for scale-up. What would be more useful would be if untreated layered crystals 4 could be exfoliated in liquids using only shear mixing. This would allow the application of the well-known strategies for the scale-up of shear mixing processes that are commonly used in industry.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such methodologies just shift the rate-limiting step from exfoliation to intercalation, limiting the potential for scale-up. What would be more useful would be if untreated layered crystals 4 could be exfoliated in liquids using only shear mixing. This would allow the application of the well-known strategies for the scale-up of shear mixing processes that are commonly used in industry.…”
Section: Main Textmentioning
confidence: 99%
“…1 Some important classes of applications, such as printed electronics, conductive coatings and composite fillers, will require industrial-scale production of defect-free graphene in a processable form. For example, graphene is likely to be used as a low-cost electrode material in applications such as solar cells, 2 batteries 3 and sensors 4 . Such electrodes will almost certainly be produced by solution-coating and so will require large quantities of graphene in the form of liquid suspensions, inks or dispersions 1 .…”
Section: Main Textmentioning
confidence: 99%
“…Linear sweep voltammetry analysis was conducted using an Autolab 302N potentiostat/galvanostat (Eco Chemie, Utrecht, The Netherlands) connected to a three-electrode cell and controlled by Nova 1.8 software. The surface area of the working electrode was 0.07 cm 2 ; as a counter, we used a platinum electrode with a larger area (approximately 2 cm 2 ). The reference was an Ag/AgCl electrode.…”
Section: Platinum Electrode Modified With Gr-au-x Nanocompositesmentioning
confidence: 99%
“…[1][2][3] As a result of its large surface area and the high mobility of its charge carriers (200,000 cm 2 /V/sec), 4 graphene enhances the electron transfer process. In addition, its two-dimensional structure is an extremely attractive support for the attachment of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The second methodology is to directly exfoliate graphite into less defective (or defect-free) single-or few-layer graphene sheets in suitable solvents by means of ultrasonic energy, microwave irradiation or other techniques. It has been reported that the solvent-exfoliated graphene dispersions can be produced by direct exfoliation of graphite in organic solvents such as DMF [86,91,92], NMP [93,94], ODCB [95] and surfactant/water solutions [96] or supercritical fluids [97]. However, the maximum concentration of graphene sheets achieved is still low (<1 mg·mL −1 ) and can only increases to 2 mg·mL −1 by a low-power sonication regime over long time frames (460 h) [94].…”
Section: Graphene Sheets In Imidazolium Ionic Liquidsmentioning
confidence: 99%